Shifting community educational orientation toward madrasah diniyah: A case study at Madrasah Diniyah Nurul Huda Pilang - ST Halimahus Sa'diyah; Nursaman (Eduvista: Journal of Education and Innovation, 2026)
The decline in community participation in madrasah diniyah has primarily been examined through the identification of contributing factors, while limited attention has been given to explaining how these factors interact to shape shifts in community educational orientation. This study aims to analyze community perceptions of the declining interest in attending Madrasah Diniyah Nurul Huda Pilang and to explain the process through which educational orientation shifts in determining children's educational priorities. A qualitative case study approach was employed using in-depth interviews, observations, documentation, and the interactive data analysis model of Miles, Huberman, and Saldaña. The findings reveal that declining participation is influenced by the increasing priority given to formal education, parental considerations, changes in children's activities in the digital era, and the need for instructional adaptation within madrasah diniyah. The interaction of these factors has shifted community educational orientation, positioning madrasah diniyah as a complementary rather than a primary form of education. This study contributes a conceptual model of shifting community educational orientation, thereby enriching the literature on non-formal Islamic education. Abstrak Menurunnya partisipasi masyarakat dalam madrasah diniyah telah banyak dikaji dari perspektif faktor-faktor penyebab, tetapi masih terbatas penelitian yang menjelaskan bagaimana berbagai faktor tersebut saling berinteraksi hingga membentuk pergeseran orientasi pendidikan masyarakat. Penelitian ini bertujuan untuk menganalisis persepsi masyarakat terhadap rendahnya minat mengikuti Madrasah Diniyah Nurul Huda Pilang serta menjelaskan proses terbentuknya pergeseran orientasi pendidikan dalam menentukan prioritas pendidikan anak. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara mendalam, observasi, dokumentasi, serta analisis data interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa rendahnya partisipasi masyarakat dipengaruhi oleh meningkatnya prioritas terhadap pendidikan formal, pertimbangan orang tua, perubahan aktivitas anak pada era digital, serta tuntutan adaptasi pembelajaran di madrasah diniyah. Interaksi berbagai faktor tersebut membentuk pergeseran orientasi pendidikan masyarakat yang menempatkan madrasah diniyah sebagai pendidikan yang bersifat komplementer, bukan lagi sebagai pilihan utama. Temuan ini memperkaya kajian pendidikan Islam nonformal melalui pengembangan model konseptual mengenai pergeseran orientasi pendidikan masyarakat.